2002
DOI: 10.2308/accr.2002.77.4.755
|View full text |Cite
|
Sign up to set email alerts
|

Insider Trading, Earnings Quality, and Accrual Mispricing

Abstract: This paper investigates whether insider trading is informative about earnings quality and the valuation implications of accruals. We show that (1) the one-year-ahead persistence of income-increasing accruals is significantly lower when accompanied by abnormal insider selling and greater when accompanied by abnormal insider buying; (2) the accrual mispricing phenomenon observed in previous work (e.g., Sloan 1996) is due to the mispricing of income-increasing accruals; (3) one-year-ahead hedge returns to trading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
257
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 420 publications
(283 citation statements)
references
References 49 publications
18
257
2
1
Order By: Relevance
“…Our sample consists of 250 largest industrial firms listed in S&P 500 Index and found the sample construe of 1 insider purchase and 4 insider sales. This concurs with prior researches that sales to purchase ratio increase with the increase in the size of the firm [15,23,25,50]. This could be mainly due to the compensation arrangement some insiders received in their employment contract.…”
Section: Multivariate Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…Our sample consists of 250 largest industrial firms listed in S&P 500 Index and found the sample construe of 1 insider purchase and 4 insider sales. This concurs with prior researches that sales to purchase ratio increase with the increase in the size of the firm [15,23,25,50]. This could be mainly due to the compensation arrangement some insiders received in their employment contract.…”
Section: Multivariate Analysissupporting
confidence: 81%
“…Studies into the sources of information asymmetry suggest that the accrual of information, R&D and analyst following have been strongly associated with the occurrence of opportunistic trading activities by insiders [16,34,35,50]. Despite these findings, there are fewer studies investigating the role of corporate policies towards insider trading activities in the capital markets [6,37].…”
Section: Why Corporate Governance?mentioning
confidence: 96%
“…Furthermore, Beneish (1999) shows that managers of firms with inflated earnings are more likely to sell their holdings and exercise stock appreciation rights than managers in control firms. Beneish and Vargus (2002) find evidence consistent with insiders trading on their knowledge of factors associated with accrual persistence, while Beneish, Press, and Vargus (2003) document that upwards earnings management occurs in firms facing higher than expected costs of default, and that insider selling and debt-covenant incentives co-exist and are complementary. On the other hand, Lakonishok and Lee (2001), who investigate insider trading activities of all companies traded on the NYSE, AMEX, andNASDAQ during 1975-1995, conclude that the informativeness of insider trading is attributable to purchases of insiders in small firms, and that insider selling has no predictive ability.…”
Section: Prior Researchmentioning
confidence: 67%
“…Many prior research shows that earnings persistence is more attributed to cash flow than accruals components of earnings, but they also report that market participants usually overact more on accruals than earnings in real investing (Sloan, 1996;Subramanyam and Wild, 1996;DeFond and Park, 2001;Xie, 2001;Beneish and Vargus, 2002;Fairfield, Whisenant and Yohn, 2003;Hanlon, 2005;Pincus et al, 2005).…”
Section: Introductionmentioning
confidence: 99%